The Effectiveness of a Multimodal Entrepreneurship Module in Enhancing Digital Business Creativity among Equality Education Learners - Shofwan, Imam; Gupta, Sachin (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2026)
Abstract: Digital business creativity has become increasingly essential for learners in non-formal equality education (Package C programs) to achieve economic empowerment in the digital era. However, entrepreneurship instruction in equality education settings remains predominantly conventional and rarely incorporates multimodal strategies tailored to diverse learner characteristics. This study examined the effectiveness of a multimodal entrepreneurship module in enhancing digital business creativity among learners in equality education. A quasi-experimental pretest-posttest control group design was employed involving 80 learners from equality education programs in Semarang Regency, Indonesia, selected through purposive sampling and grouped into an experimental group (n = 40) and a control group (n = 40). The experimental group participated in an eight-week multimodal intervention integrating visual, auditory, digital simulation, and project-based learning activities, while the control group received conventional instruction. Data were collected using the adapted Digital Business Creativity Scale (DBCS), which demonstrated satisfactory reliability (Cronbach’s α = .87). Independent samples t-test and ANCOVA results indicated a significant difference in post-test scores between groups, F(1,77) = 88.42, p < .001, partial η² = .53, with a large effect size (Cohen’s d = 1.21). The intervention significantly improved learners’ digital ideation, innovation, content creation, and digital problem-solving skills. These findings provide empirical evidence that multimodal entrepreneurship pedagogy can serve as an effective instructional strategy for strengthening entrepreneurial empowerment in non-formal equality education contexts. Keywords: multimodal learning, entrepreneurship education, digital creativity, equality education, nonformal education